2014
DOI: 10.1186/2049-6958-9-12
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of serum and pleural levels of adenosine deaminase 1–2, and interferon-γ in the diagnosis of pleural tuberculosis

Abstract: BackgroundTo evaluate and compare the diagnostic efficiency of serum (s) and pleural (p) levels of adenosine deaminase (ADA)-1, ADA-2, total ADA, and interferon-gamma (IFN-γ) for the differential diagnosis of pleural tuberculosis (TB).MethodsClinical and analytic data of 93 consecutive patients with pleural effusions from May 2012 to February 2013 were prospectively evaluated. The study population included 43 pleural TB, 23 malignancies, and 27 other exudates. The median and interquartile range of ADA-1, ADA-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Importantly, the diagnostic accuracy of ADA is unaffected by the presence of HIV infection . Use of the ADA‐2 isoenzyme assay increases the test's specificity for TB, which may be useful where there is the potential for a false positive result such as in bacterial pleural infection, chronic rheumatoid effusions, mesothelioma, lung cancer and haematological malignancies . One‐third of parapneumonic effusions and two‐thirds of empyemas have ADA levels exceeding 40 IU/L .…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the diagnostic accuracy of ADA is unaffected by the presence of HIV infection . Use of the ADA‐2 isoenzyme assay increases the test's specificity for TB, which may be useful where there is the potential for a false positive result such as in bacterial pleural infection, chronic rheumatoid effusions, mesothelioma, lung cancer and haematological malignancies . One‐third of parapneumonic effusions and two‐thirds of empyemas have ADA levels exceeding 40 IU/L .…”
Section: Diagnosismentioning
confidence: 99%
“…Assays that directly quantify the amount of IFN‐γ in pleural fluid (so‐called ‘unstimulated’ IFN‐γ) have a high sensitivity (89%) and specificity (97%) for tuberculous effusions, and may be superior to ADA . An IFN‐γ concentration above 140 pg/mL has a sensitivity of 94% for TB effusion and a concentration above 240 pg/mL has a sensitivity of 95% . Recently, the combination of high ADA and IFN‐γ was reported to have a specificity and PPV of 100% .…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of unstimulated IFN‐γ in pleural fluid at a concentration of greater than 140 pg/mL has a sensitivity and specificity of 94% and 92% for TB pleural effusion. These values increased to 95% and 96% when the cut‐off value of 240 pg/mL was used . In a meta‐analysis, the sensitivity of the IFN‐γ assay for TB pleural effusion was 89%, and the specificity 97% .…”
Section: Pleural Fluid Characteristicsmentioning
confidence: 99%
“…Its chief role concerns the proliferation and differentiation of lymphocytes and activation of macrophages [11]. Hence it is considered as a good marker for cell immunity [12]. It is also considered to be an important enzyme for modulating the bioactivity of insulin [13] and some studies have reported it to be a predictive marker of insulin resistance [14].…”
Section: Introductionmentioning
confidence: 99%